PENGENDALIAN MUTU TENAGA PENDIDIK BIDANG PENDIDIKAN DASAR DINAS PENDIDIKAN KABUPATEN KUTAI TIMUR - Agus Kusmawati (ADMINISTRASI PUBLIK, 2020)
A qualified teacher is a person who has special abilities and expertise in the field of teacher training so that he is able to perform his duties and functions as a teacher with maximum abilities. In other words qualified teachers are people who are well educated and well trained and have rich experience in their fields.During elementary school, it should be sought for children to be free to receive their knowledge as well as possible and truly. The school environment is a place that is very influential on the potential for the development of primary school children learning into a better realm as set by the government towards the goals of education in primary and secondary schools can be realized.The teaching and learning process is the core of the overall education process with the teacher as a science developer. Interaction or reciprocity between teachers and students is one of the most important and mandatory factors in the world of education, because the results of that interaction will produce a quality Human Resources.Education in primary schools as formal education for future generations of children in the nation based on the character and culture of the nation which is then determined through the curriculum, then from this curriculum the wheels of education are spurred and implemented.Student learning progress. The goal is mainly to find out how the learning process takes place, know the process of coaching and coaching to students, measuring the effectiveness and efficiency of the administration of education, as well as measuring the progress and development of student learning outcomes. The suitability of the curriculum with the dynamics of the demands of the community's needs, the achievement of students' abilities based on established school culture standards, the availability of learning resources that are relevant to the demands of the curriculum, the coverage of local content in accordance with the needs of the local area, as well as the smooth implementation of the school curriculum as a whole as well as the teacher and education staff the other.In terms of effectiveness, it is clear that the system of subject teachers is more effective than the classroom teacher system. Because every teacher can choose subjects that are really mastered. Even teachers can also choose subjects according to the disciplines they learn while studying.